FAKTOR-FAKTOR YANG MEMPENGARUHI CASH HOLDING PADA PERUSAHAAN MANUFAKTUR - Ivone Margaretha, Sofia Prima Dewi (Jurnal Paradigma Akuntansi, 2020)
The purpose of this empirical research is to examine about the effect of profitability, firms size, leverage, and capital expenditure on cash holding in manufacturing companies listed on the Indonesia Stock Exchange from 2015 to 2017. The research used 60 manufacturing companies that were selected using purposive sampling method for a total of 180 data in three years. Data processing techniques used are Eviews version 9.0. This research used panel data regression analysis. The results of this research shows profitability, leverage, and capital expenditurehave effects on cash holding, and firm size have no effect on cash holding. Siggestions that can be given are for further research to be expected to use other independent variables such as liquidity, cash flow, working capital, inventory turnover, and dividend payment that may show better results.